THE INFLUENCE OF WORK LIFE BALANCE, EMPLOYEE ENGAGEMENT AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE OF PT ASABRI (PERSERO) BRANCH OFFICE - Putri, Mulia; Absah, Yeni; Silalahi, Amlys Syahputra (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to determine the influence of work life balance, employee engagement and job satisfaction in improving the employee performance of PT ASABRI (Persero) Branch Office both partially and simultaneously. The research method used is a quantitative method using a 1-5 Likert scale analysis tool which is then tested. The data collection technique in this research uses a questionnaire distributed via a Google Form link. The population in this study were all employees who worked at PT ASABRI (Persero) Branch Office, totaling 363 people. The sample size in this study was 190 determined using the Slovin formula. The sampling method used was nonprobability sampling using proportional random sampling. The results of this research show that work life balance, employee engagement and job satisfaction partially and simultaneously have a positive and significant effect in improving the employee performance of PT ASABRI (Persero) Branch Office